2022
DOI: 10.2217/imt-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome in a Patient with Metastatic Renal Cell Carcinoma Treated with Pembrolizumab Plus Axitinib

Abstract: We report the case of a patient with metastatic renal cell carcinoma who developed Takotsubo syndrome (TTS) 6 days after starting pembrolizumab plus axitinib as first-line treatment. Coronary angiogram was negative for obstructive coronary artery disease and echocardiogram revealed a depressed left ventricular ejection fraction with apical akinesis. Axitinib was discontinued and myocardial contractile function fully recovered 23 days after the initial presentation. The treatment was safely resumed and granted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Regarding time of TTS presentation, there are lines of evidence in our review (median time on immunotherapy at the time of TTS presentation was found to be 77 days) and in other studies [11,29] denoting that immune-related TTS represents a rather delayed form of cardiotoxicity. However, we believe that these observations may be biased from the small sample size.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Regarding time of TTS presentation, there are lines of evidence in our review (median time on immunotherapy at the time of TTS presentation was found to be 77 days) and in other studies [11,29] denoting that immune-related TTS represents a rather delayed form of cardiotoxicity. However, we believe that these observations may be biased from the small sample size.…”
Section: Discussionsupporting
confidence: 51%
“…Other possible stressors included the presence of non-cardiac irAEs [15,[17][18][19]23,26,28,29], infections [21], and infusion reactions [16]. Other risk factors, such as active smoking and cardiovascular comorbidities, have been previously described [14] and were also identified in our study [17][18][19].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations